Effect of Introduction of a Lactation Counselor on Breastfeeding Uptake and Satisfaction in an Urban Prenatal Clinic [39A]. Issue 1 (May 2017) - Martinez, Noelle; Nguyen, Antoinette; Hu, Fengling; Strohbach, Angelina; Hajjar, Nadia; Yee, Lynn
Abstract : INTRODUCTION: To assess the association between introduction of a full-time lactation counselor (LC) and breastfeeding outcomes. METHODS: This is a prospective observational study of low-income, minority women receiving care in a publicly funded prenatal clinic 6 months before and after introduction of a LC. The LC provided inpatient and outpatient one-on-one antenatal and postpartum lactation education and support. Chart review and survey data were collected to compare women receiving care before versus after LC introduction. The primary outcome was breastfeeding continuation (exclusive or partial) at 6 weeks postpartum; secondary outcomes included breastfeeding comfort, confidence, and training satisfaction. Bivariable and multivariable analyses were utilized as appropriate. RESULTS: Of 218 women, 54.6% were post-LC introduction; there were no demographic differences between cohorts. Factors associated with breastfeeding continuation included greater maternal education (aOR 4.10, 95% CI 1.73-9.69) and breastfeeding comfort and confidence (aOR 3.04, 95% CI 1.34-6.91; aOR 4.56, 95% CI 1.81-11.46). Women with LC were more likely to be satisfied with BF training (98.2% vs 84.5%, p=.01), and were more likely to have performed any breastfeeding (89.7% vs 73.6%, p=.007), which remained significant on regression analysis (aOR 3.41, 95% CI 1.35-8.63). However, LC was not associated with continued BF at 6 weeks (aOR 1.28, 95% CI 0.69-2.38). CONCLUSION: Continued breastfeeding at 6 weeks postpartum among low-income, minority women was associated with greater maternal education and with breastfeeding comfort and confidence. Lactation counselor introduction was associated with improved breastfeeding training satisfaction and increased rates of any breastfeeding, but was not associated with continued breastfeeding at 6 weeks.